HEAVY METALS ON TECHNOGENIC OBJECTS OF MINING AND PROCESSING ENTERPRISES OF THE KRYVYI RIG BASIN - Коshаrnа S.; Коrzhnev M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The goal of the paper is to determine and explain the patterns of distribution of heavy metals in the territories of ore mining and processing enterprises in Kryvyi Rig and to substantiate the legitimacy of applying the method of semiquantitative atomic emission spectral analysis in such studies. Methodology. In the course of the study, various methods of spectral analysis (semiquantitative atomic emission and atomic absorption using 0.5 M HCl and 2 M HNO3) were used in the analysis of soil contamination, and their comparison was made. Results. The content and distribution of heavy metals in soils at the sites of mining and processing enterprises depends primarily on the share of different sedimentary material in them. These are: material of the weathering crust of granites and rocks of greenstone belts of the Middle Dnieper, as well as rocks of the Kryvyi Rig series; products of iron ore beneficiation at mining and processing enterprises and sediments formed during discharge of highly mineralized mine and industrial waters of enterprises; material of slags and smokes of metallurgical enterprises, introduced by the wind; products of domestic waste treatment. The main sources of heavy metals in the soils of the Kryvyi Rig are slags and smokes of metallurgical enterprises. Such a source cannot be the sludge of processing enterprises because of the low content of impurity elements in iron banded formations, including heavy metals. When heavy metals fall onto the soil, their redistribution occurs under the influence of wind and atmospheric precipitation, with the transfer and accumulation of clay-scale particles, the main concentrators of heavy metals, into the lower places of the relief. In general, this leads to the dispersion of heavy metals in soils. Scientific novelty. The factors of geochemical migration of heavy metals within the local geochemical arenas of ore mining and processing enterprises are determined. Practical significance. The educed conformities to law of migration of heavy metals open possibility of more exact prognosis of their distribution in soils on the objects of mining and processing enterprises.